Ultrahigh-pore-density cordierite ceramic material and preparation method thereof
Through the combination of specific compositions of inorganic solid components and cellulose ethers, combined with extrusion molding, microwave drying and other processes, ultra-high pore density cordierite ceramic materials were successfully prepared, solving the problems of high production difficulties and many appearance defects in the prior art, and achieving efficient and low-cost production results.
Patent Information
- Application Number
- CN202510336185.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-21
- Publication Date
- 2025-04-18
AI Technical Summary
It is difficult to effectively prepare ultra-high pore density cordierite ceramic materials in the prior art, especially in extrusion molding. Due to the fine particle size of the raw material and the thin wall thickness, the extrusion pressure is large, the speed is slow, and the appearance defects are many.
Ultra-high pore density cordierite ceramic materials are prepared by mixing, kneading and extruding processes using inorganic solid components and cellulose ethers of specific compositions. The specific steps include mixing the inorganic solid components with cellulose ether, adding water for a first kneading, followed by adding a lubricant and a moisturizer for a second kneading, forming a plastic clay material, and obtaining the final material by extrusion, microwave drying and cutting.
The extrusion molding of high pore density and thin-walled ceramics is achieved, which reduces firing and shrinkage, avoids appearance defects, improves the pass rate and production efficiency of the products, and reduces production costs.
Smart Images

Figure CN119841659A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ceramic materials, and in particular to an ultra-high pore density cordierite ceramic material and a preparation method thereof. Background Art
[0002] Ultra-high pore density ceramics have a very high geometric specific surface area. Combined with the unique characteristics of ceramic materials such as high temperature resistance, high strength, and good chemical stability, they are currently widely used in environmental protection, energy conservation, medical treatment, aerospace, thermoacoustic refrigeration, reforming hydrogen production, and other fields. Ultra-high pore density ceramics have a large number of geometric pores and a high geometric specific surface area, which provides a higher loading area for reforming hydrogen production catalysts and can significantly improve the catalytic conversion efficiency.
[0003] The traditional molding process of cordierite ceramics is extrusion molding. The cordierite ceramics currently on the market have a maximum pore density of 900 cpsi and a wall thickness of 2 mil, which is generally less than 1000 cpsi. This is because as the pore density increases, the wall thickness needs to be thinned, and the difficulty of extrusion molding increases significantly. Because during the extrusion molding process, although the particle size of the raw materials is smaller than the width of the mold slot, there will be a bridging effect between the raw materials, which makes it difficult for the raw materials to be smoothly extruded through the narrow slot of the mold. This may lead to high extrusion pressure, slow extrusion speed, and many defects in the extrusion appearance. Therefore, the material properties and raw material performance requirements of high pore density and thin-walled honeycomb ceramic mud are relatively high. At present, 3D printing, template method and other technologies are generally used for ultra-high pore density honeycomb ceramics, and it is difficult to use traditional extrusion molding methods. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide an ultra-high pore density cordierite ceramic material and a preparation method thereof.
[0005] The technical solution of the present invention to solve the above technical problems is as follows: The present invention provides a cordierite ceramic material with ultra-high pore density, wherein the raw materials of the ceramic material include inorganic solid components, and the inorganic components include talc, kaolin, kyanite, boehmite, alumina, and silicon dioxide; The particle size of the talc is D 50 1-10μm, particle size D 97 ≤30μm; the particle size of the kaolin is D 50 1-5μm, particle size D 97 ≤15μm; the particle size of the kyanite D 50 1-5μm, particle size D 97 ≤15μm; the particle size of the boehmite D 50 0.5-4μm, particle size D 97 ≤10μm; the particle size of the aluminum oxide D 50 1-10μm, particle size D97 ≤30μm; the particle size of the silicon dioxide D 50 1-10μm, particle size D 97 ≤30μm.
[0006] Based on the above technical solution, the present invention can also be improved as follows.
[0007] Furthermore, the microstructure of the talc is spherical or flaky, the microstructure of the kaolin is spherical or flaky, the microstructure of the boehmite is spherical, the microstructure of the alumina is spherical, and the microstructure of the silica is spherical.
[0008] Furthermore, in the inorganic solid component, the mass percentage of the talc is 41%-42%, the mass percentage of the kaolin is 8%, the mass percentage of the kyanite is 10%-22%, the mass percentage of the boehmite is 3%-6%, the mass percentage of the alumina is 17%-26%, the mass percentage of the silica is 10%-15%, and the total mass percentage of each component is 100%.
[0009] Furthermore, the raw material also includes cellulose ether, and based on the mass of the inorganic component being 100%, the mass percentage of the cellulose ether is 5%.
[0010] Furthermore, the pore density of the ceramic material is 950-60000 cpsi and the wall thickness is 0.04-0.10 mm.
[0011] The present invention also provides a method for preparing the ultra-high pore density cordierite ceramic material as described above, which is prepared by using the raw materials.
[0012] Further, the inorganic solid component is mixed with cellulose ether to obtain powder; water is then added for a first kneading to obtain a first kneaded material, and a lubricant and a moisturizer are added for a second kneading to obtain a plastic mud material; the mud material is sequentially extruded, microwave dried, and cut to obtain the ultra-high pore density cordierite ceramic material.
[0013] Furthermore, the extrusion pressure of the extrusion is 5-13 MPa, and the extrusion speed is 10-35 mm / s.
[0014] Furthermore, based on the mass of the powder being 100%, the mass percentage of water is 30%; based on the mass of the first kneaded material being 100%, the mass percentage of the lubricant is 1%, and the mass percentage of the humectant is 1%.
[0015] Furthermore, the lubricant is stearate, and the moisturizing agent is glycerol.
[0016] The beneficial effects of the present invention are: (1) The ultra-high pore density cordierite ceramic material of the present invention has a fine particle size of each component in the inorganic solid component of the raw material, which can ensure that the high pore density and thin-walled ceramic can be prepared by extrusion molding; (2) The ultra-high pore density cordierite ceramic material of the present invention introduces kyanite into the raw material, which effectively reduces the firing shrinkage and avoids deformation or other appearance defects after firing caused by the use of fine-grained components, so that the ceramic material prepared under the extrusion molding process has a better appearance and improves the qualified rate of the product; (3) The ultra-high pore density cordierite ceramic material of the present invention, the introduction of kyanite effectively reduces the production cost; (4) The ultra-high pore density cordierite ceramic material of the present invention has the characteristics of ultra-high pore density and ultra-thin wall. The ultra-high pore density not only has more reaction channels, but also has ultra-thin walls, which can provide a larger specific surface area, providing a larger specific surface area for catalyst coating and catalytic conversion; (5) The method for preparing the ultra-high pore density cordierite ceramic material of the present invention has the advantages of fast molding speed, low pressure, high firing qualification rate and low production cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a scanning electron microscope image of the ultra-high pore density cordierite ceramic material of the present invention, Example 3; Figure 2 This is an appearance diagram of Example 7 of the ultra-high pore density cordierite ceramic material of the present invention; Figure 3 This is the appearance diagram of the ultra-high pore density cordierite ceramic material of the present invention, comparative example 1. DETAILED DESCRIPTION
[0018] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0019] The ultra-high pore density cordierite ceramic material of the present invention comprises inorganic solid components, wherein the inorganic components comprise talc, kaolin, kyanite, boehmite, alumina and silicon dioxide; the particle size of the talc is D 50 1-10μm, particle size D 97 ≤30μm; Kaolin particle size D 50 1-5μm, particle size D 97 ≤15μm; Kyanite particle size D 50 1-5μm, particle size D 97 ≤15μm; boehmite particle size D 50 0.5-4μm, particle size D 97 ≤10μm; Particle size of alumina D50 1-10μm, particle size D 97 ≤30μm; Particle size of silicon dioxide D 50 1-10μm, particle size D 97 ≤30μm.
[0020] The ultra-high pore density cordierite ceramic material of the present invention has finer particle sizes of various components in the raw materials, which can ensure that high-pore density and thin-walled ceramics can be prepared by extrusion molding. At the same time, kyanite is introduced into the raw materials, which effectively reduces the firing shrinkage and avoids deformation or other appearance defects after firing due to the use of fine-grained components, so that the ceramic material prepared under the extrusion molding process has a better appearance and improves the qualified rate of the products; the introduction of kyanite also effectively reduces the production cost, and other components can also ensure to varying degrees that when the raw material particle size is fine, the ceramic material has a fast molding speed, low pressure, a high firing qualified rate, and a low production cost.
[0021] Specifically, kyanite will decompose into mullite and silica during the high-temperature firing process, accompanied by volume expansion, which offsets the firing shrinkage caused by the use of extremely fine raw materials and reduces the overall firing shrinkage of ceramic materials. It not only solves the problems of low pass rate such as firing deformation, bending, cracking, etc., but also solves the problem of increasing the extrusion speed and reducing the extrusion pressure.
[0022] Preferably, the microstructure of talc is spherical or flaky, the microstructure of kaolin is spherical or flaky, the microstructure of boehmite is spherical, the microstructure of alumina is spherical, and the microstructure of silica is spherical; the microstructures of the above components can further increase the extrusion speed.
[0023] Further preferably, the microstructure and specific particle size of each component in the inorganic solid component are as follows: Talc A: spherical, D 50 1-5μm, D 97 ≤15μm; Talc B: flake, D 50 1-5μm, D 97 ≤15μm; Talc C: flake, D 50 6-10μm, D 97 ≤30μm; Kaolin A: spherical, D 50 1-5μm, D 97 ≤15μm; Kaolin B: flake, D 50 1-5μm, D 97 ≤15μm; Kyanite A:D 50 1-5μm, D97 ≤15μm; Boehmite A: spherical, D 50 0.5-4μm, D 97 ≤10μm; Alumina A: spherical, D 50 1-5μm, D 97 ≤10μm; Alumina B: spherical, D 50 6-10μm, D 97 ≤30μm; Silica A: spherical, D 50 1-5μm, D 97 ≤10μm; Silica B: spherical, D 50 6-10μm, D 97 ≤30μm.
[0024] Preferably, in the inorganic solid components, the mass percentage of talc is 41%-42%, the mass percentage of kaolin is 8%, the mass percentage of kyanite is 10%-22%, the mass percentage of boehmite is 3%-6%, the mass percentage of alumina is 17%-26%, the mass percentage of silica is 10%-15%, and the total mass percentage of each component is 100%; the formula of the above-mentioned components can effectively reduce the risk of large shrinkage of ceramic materials during firing, so that when the raw material particle size is fine, it still has the advantages of fast molding speed, low pressure and high firing qualification rate.
[0025] Further preferably, in the inorganic solid component, the mass percentage of talc is 41.4%-41.9%, the mass percentage of aluminum oxide is 17.8%-25.1%, and the mass percentage of silicon dioxide is 10.8%-15%.
[0026] Preferably, the raw materials also include cellulose ether, and the mass percentage of cellulose ether is 5% based on the mass of the inorganic component being 100%. Cellulose ether has good water retention, which helps to reduce extrusion pressure and increase extrusion speed.
[0027] Preferably, the pore density of the ceramic material is 950-60000 cpsi and the wall thickness is 0.04-0.10 mm; the ceramic material has the characteristics of ultra-high pore density and ultra-thin wall. The ultra-high pore density not only has more reaction channels, but also the superimposed ultra-thin wall can provide a larger specific surface area, providing a larger specific surface area for catalyst coating and catalytic conversion.
[0028] Further preferably, the shape of the honeycomb lattice in the honeycomb structure of the ceramic material is not particularly limited. A single hole shape such as circular, triangular, quadrilateral, hexagonal, etc. can be adopted, or a variety of hole shapes such as circular, quadrilateral, hexagonal, asymmetric, etc. can be adopted. It is not necessary to adopt a single hole shape in the honeycomb structure, and it is preferred to adopt, for example, quadrilateral holes.
[0029] The preparation method of the ultra-high pore density cordierite ceramic material of the present invention is prepared by adopting the above raw materials, and the specific steps are: mixing the inorganic solid component with the cellulose ether to obtain a powder; then adding water for the first kneading to obtain a first kneaded material, and then adding a lubricant and a moisturizer for the second kneading to obtain a clay material with plasticity; and sequentially extruding, microwave drying and cutting the clay material to obtain the ultra-high pore density cordierite ceramic material.
[0030] The ceramic material prepared by the preparation method of the present invention has good appearance and qualified rate, and the preparation efficiency is greatly improved due to the high extrusion speed.
[0031] Preferably, based on the mass of the powder being 100%, the mass percentage of water is 30%; based on the mass of the first kneaded material being 100%, the mass percentage of the lubricant is 1%, and the mass percentage of the humectant is 1%.
[0032] Preferably, the lubricant is stearate and the humectant is glycerol.
[0033] Preferably, the extrusion pressure is 5-13 MPa and the extrusion speed is 10-35 mm / s; the low extrusion pressure and high extrusion speed effectively improve the basic efficiency.
[0034] The present invention is illustrated below by means of specific examples.
[0035] Examples 1-9 and comparative examples 1-4 are all prepared using the preparation method of the present invention. The specific composition ratios of each example and comparative example are shown in Table 1, the specific particle size of each inorganic solid component is shown in Table 2, and the performance test results of each example and comparative example are shown in Table 3.
[0036] Table 1 Specific composition ratios of various embodiments and comparative examples In Table 1, the mass percentage of cellulose ether is based on the total mass of inorganic solid components as 100%, the lubricant and humectant are both based on the total mass of the first kneaded material as 100%, the lubricant is stearate, and the humectant is glycerol.
[0037] Table 2 Particle size of inorganic solid components in various examples and comparative examples In Table 2, the particle sizes of the inorganic solid components are as follows: talc A: spherical, D 50 1-5μm, D 97 ≤15μm; Talc B: flake, D 50 1-5μm, D 97 ≤15μm; Talc C: flake, D 50 6-10μm, D 97 ≤30μm. Kaolin A: spherical, D 50 1-5μm, D 97 ≤15μm; Kaolin B: flake, D 50 1-5μm, D 97 ≤15μm. Kyanite A:D 50 1-5μm, D 97 ≤15μm; Boehmite A: spherical, D 50 0.5-4μm, D 97 ≤10μm. Alumina A: spherical, D 50 1-5μm, D 97 ≤10μm; Alumina B: spherical, D 50 6-10μm, D 97 ≤30μm. Silica A: spherical, D 50 1-5μm, D 97 ≤10μm; Silica B: spherical, D 50 6-10μm, D 97 ≤30μm.
[0038] Table 3 Performance test results of various embodiments and comparative examples The scanning electron microscope photo of the ceramic material of Example 3 is shown in FIG. Figure 1 As shown, the appearance of the ceramic material of Example 7 is as follows Figure 2 As shown, the appearance of the ceramic material of Comparative Example 1 is as follows Figure 3 shown.
[0039] In general ceramic raw materials, the finer the particle size, the greater the ceramic sintering shrinkage. According to Table 3 and Figure 1-3 It can be seen that with the increase in the amount of kyanite added, the firing shrinkage is significantly reduced, the firing pass rate is also increased, and the appearance of the ceramic material is also significantly improved. This is because the introduction of an appropriate amount of kyanite is converted into mullite during the high-temperature firing process, and the volume expands accordingly, offsetting part of the firing shrinkage caused by the use of ultrafine raw materials.
[0040] At the same time, the reduction of defects such as deformation and bending of the honeycomb structure of ceramic materials can increase the bonding strength of the green body, and the thermal shock resistance stability is also improved accordingly. However, the amount of kyanite added cannot be increased infinitely. As its addition amount increases, the thermal shock resistance stability shows a trend of first increasing and then decreasing. This is because kyanite contains certain impurities, which reduces the performance of honeycomb ceramics and reduces the thermal shock resistance stability.
[0041] The present invention uses spherical and quasi-spherical raw materials with good fluidity as much as possible, and selects fine-grained raw materials as much as possible, the main purpose of which is to reduce extrusion pressure, increase extrusion speed, and reduce production costs. It can be seen from the comparison of the embodiments and the comparative examples that the finer the particle size and the more rounded the morphology of the raw materials, the extrusion pressure will be significantly reduced, and the extrusion speed will also increase accordingly. Even if some flaky coarse-grained raw materials are used, although the material particle size is smaller than the wall thickness, factors such as the bridging effect and friction in extrusion molding may still lead to a situation where extrusion molding cannot be produced, as shown in Comparative Example 3.
[0042] In order to reduce the difficulty of extrusion molding, the present invention simultaneously uses stearate with good lubricity as a lubricant, and uses cellulose ether with good water retention and glycerol as a moisturizer to increase the plasticity of the mud, reduce the extrusion pressure and increase the extrusion speed.
[0043] In the description of the present invention, it should be noted that the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0044] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. An ultra-high pore density cordierite ceramic material, characterized in that: The raw materials of the ceramic material include inorganic solid components, and the inorganic components include talc, kaolin, kyanite, boehmite, alumina, and silicon dioxide; The particle size of the talc is D 50 1-10μm, particle size D 97 ≤30μm; the particle size of the kaolin is D 50 1-5μm, particle size D 97 ≤15μm; the particle size of the kyanite D 50 1-5μm, particle size D 97 ≤15μm; the particle size of the boehmite D 50 0.5-4μm, particle size D 97 ≤10μm; the particle size of the aluminum oxide D 50 1-10μm, particle size D 97 ≤30μm; the particle size of the silicon dioxide D 50 1-10μm, particle size D 97 ≤30μm.
2. The ultra-high pore density cordierite ceramic material according to claim 1, characterized in that: The microstructure of the talc is spherical or flaky, the microstructure of the kaolin is spherical or flaky, the microstructure of the boehmite is spherical, the microstructure of the alumina is spherical, and the microstructure of the silicon dioxide is spherical.
3. The ultra-high pore density cordierite ceramic material according to claim 2, characterized in that: Among the inorganic solid components, the mass percentage of talc is 41%-42%, the mass percentage of kaolin is 8%, the mass percentage of kyanite is 10%-22%, the mass percentage of boehmite is 3%-6%, the mass percentage of alumina is 17%-26%, the mass percentage of silica is 10%-15%, and the total mass percentage of each component is 100%.
4. The ultra-high pore density cordierite ceramic material according to claim 1, characterized in that: The raw materials also include cellulose ether. Based on the mass of the inorganic component being 100%, the mass percentage of the cellulose ether is 5%.
5. The ultra-high pore density cordierite ceramic material according to any one of claims 1 to 4, characterized in that: The ceramic material has a pore density of 950-60000 cpsi and a wall thickness of 0.04-0.10 mm.
6. A method for preparing the ultra-high pore density cordierite ceramic material according to any one of claims 1 to 5, characterized in that: The method is prepared by adopting the raw materials.
7. The method for preparing an ultra-high pore density cordierite ceramic material according to claim 6, characterized in that: The inorganic solid component is mixed with cellulose ether to obtain powder; water is then added for a first kneading to obtain a first kneaded material, and a lubricant and a moisturizer are added for a second kneading to obtain a plastic mud material; the mud material is sequentially extruded, microwave dried, cut, and sintered to obtain the ultra-high pore density cordierite ceramic material.
8. The method for preparing an ultra-high pore density cordierite ceramic material according to claim 7, characterized in that: The extrusion pressure of the extrusion is 5-13 MPa, and the extrusion speed is 10-35 mm / s.
9. The method for preparing an ultra-high pore density cordierite ceramic material according to claim 7, characterized in that: Based on the mass of the powder being 100%, the mass percentage of water is 30%; based on the mass of the first kneaded material being 100%, the mass percentage of the lubricant is 1%, and the mass percentage of the humectant is 1%.
10. The method for preparing an ultra-high pore density cordierite ceramic material according to claim 9, characterized in that: The lubricant is stearate, and the humectant is glycerol.
Citation Information
Patent Citations
Cordierite honeycomb ceramic material with low heat capacity and high specific surface area and preparation method
CN119219403A
Method of producing cordierite bodies utilizing substantially reduced firing times
CN1210835A
Fabrication of ultra-thinwall cordierite structures
CN1379744A